A high‐performance gradient insert for rapid and short‐T2 imaging at full duty cycle. Issue 6 (5th October 2017) - Weiger, Markus; Overweg, Johan; Rösler, Manuela Barbara; Froidevaux, Romain; Hennel, Franciszek; Wilm, Bertram Jakob; Penn, Alexander; Sturzenegger, Urs; Schuth, Wout; Mathlener, Menno; Borgo, Martino; Börnert, Peter; et al.
Abstract : Purpose: The goal of this study was to devise a gradient system for MRI in humans that reconciles cutting‐edge gradient strength with rapid switching and brings up the duty cycle to 100% at full continuous amplitude. Aiming to advance neuroimaging and short‐T2 techniques, the hardware design focused on the head and the extremities as target anatomies. Methods: A boundary element method with minimization of power dissipation and stored magnetic energy was used to design anatomy‐targeted gradient coils with maximally relaxed geometry constraints. The design relies on hollow conductors for high‐performance cooling and split coils to enable dual‐mode gradient amplifier operation. With this approach, strength and slew rate specifications of either 100 mT/m with 1200 mT/m/ms or 200 mT/m with 600 mT/m/ms were reached at 100% duty cycle, assuming a standard gradient amplifier and cooling unit. Results: After manufacturing, the specified values for maximum gradient strength, maximum switching rate, and field geometry were verified experimentally. In temperature measurements, maximum local values of 63°C were observed, confirming that the device can be operated continuously at full amplitude. Testing for peripheral nerve stimulation showed nearly unrestricted applicability in humans at full gradient performance. In measurements of acoustic noise, a maximum average sound pressure level of 132 dB(A) was determined. In vivo capability was demonstrated by head and knee imaging. Full gradient performance was employed with echo planar and zero echo time readouts. Conclusion: Combining extreme gradient strength and switching speed without duty cycle limitations, the described system offers unprecedented options for rapid and short‐T2 imaging. Magn Reson Med 79:3256–3266, 2018. © 2017 International Society for Magnetic Resonance in Medicine.